Case series of Fetus in fetu- Variable presentation - Mathur, Geetika; Gupta, Pradeep; Nazimhusein Tinwala, Hafeza; Saini, Girish; Kumar Shukla, Arvind; Ratendra Singh (Journal of Neonatal Surgery, 2025)
Background: Fetus in fetu is a rare congenital anomaly. It comprises of a malformed twin incorporated into the surviving twin. Materials and method: Diagnosis is made preoperatively through ultrasonography, plain radiography, computed tomography or MRI. Histopathology confirms the diagnosis; here we are reporting a series of four cases of fetus in fetu. Conclusion: Treatment is en-bloc excision. Histopathology will lead to further line of treatment.